LB0004 METHOTREXATE WITHDRAWAL IN PATIENTS WITH RHEUMATOID ARTHRITIS WHO ACHIEVE LOW DISEASE ACTIVITY WITH TOFACITINIB MODIFIED-RELEASE 11 MG ONCE DAILY + METHOTREXATE: A RANDOMISED NON-INFERIORITY PHASE 3B/4 STUDY. (June 2019) - B. Cohen, Stanley; Pope, Janet; Haraoui, Boulos; Irazoque-Palazuelos, Fedra; Korkosz, Mariusz; Diehl, Annette; Luis Rivas, Jose; Lukic, Tatjana; Liu, Shixue; Stockert, Lori; Iikuni, Noriko; Keystone, Edward
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). The impact of methotrexate (MTX) withdrawal in patients (pts) with RA who achieve low disease activity (LDA) or remission following treatment with tofacitinib in combination with MTX is unclear. Objectives: To compare the efficacy and safety of tofacitinib modified-release (MR) 11 mg once daily (QD) with and without MTX in pts with RA who have achieved LDA with tofacitinib and MTX. Methods: ORAL Shift (NCT02831855 ) was a global Phase 3b/4 study in pts aged ≥18 years with moderate to severe RA and an inadequate response to MTX. Pts received open-label (OL) tofacitinib MR 11 mg QD with MTX (tofacitinib + MTX) for 24 weeks. Pts achieving LDA (CDAI ≤10) at Week (W)24 entered the 24-week double-blind (DB) MTX withdrawal phase and were randomised 1:1 to receive tofacitinib MR 11 mg QD with placebo (tofacitinib monotherapy; ie underwent blinded MTX withdrawal) or continue tofacitinib + MTX. The primary endpoint was least squares mean change from W24 to W48 (Δ; DB phase) in DAS28 4(ESR). Non inferiority of tofacitinib monotherapy vs tofacitinib + MTX was declared if the upper bound of the 95% two-sided confidence interval (CI) for the difference in ΔDAS28-4(ESR) between arms was <0.6. Secondary endpoints included ΔDAS28-4(CRP), ΔSDAI, ΔCDAI, ΔHAQ-DI; rates of ACR20/50/70 response, HAQ-DI response, DAS28-4(ESR)- and CDAI-defined LDA and remission, and ACR-EULAR Boolean-defined 1 remission (W48); and safety (OL and DB phases). Results: Of 694 pts in the OL phase, 530 achieved CDAI-defined LDA at W24 and were treated in the DB phase (tofacitinib monotherapy: n=264; tofacitinib + MTX: n=266). Demographics and pt characteristics at OL-phase baseline were similar between treatment arms. The difference (95% CI) between arms in ΔDAS28 4(ESR) (primary endpoint) was 0.30 (0.12, 0.48; Table 1) at W48, demonstrating that tofacitinib monotherapy was non-inferior to tofacitinib + MTX. Consistent with the primary endpoint, ΔDAS28-4(CRP)/SDAI/CDAI were greater for tofacitinib monotherapy vs tofacitinib + MTX, but these differences were not clinically meaningful; ACR/HAQ-DI response and LDA rates were generally similar between arms (Table). Remission rates were also similar between arms and generally did not change after MTX withdrawal. In the DB phase, rates of AEs, serious AEs, discontinuations due to AEs and AEs of special interest were generally comparable between arms (Table 1). Conclusion: Pts receiving tofacitinib MR 11 mg QD + MTX who achieve LDA may withdraw MTX up to W48 without significant worsening of disease activity. Pts in remission tend to remain in remission after MTX withdrawal. Safety appeared consistent with the known profile of tofacitinib. Reference: [1] Felson DT et al. Arthritis Rheum 2011;63:573-586 Acknowledgement: Study sponsored by Pfizer Inc. Medical writing support was provided by C Viegelmann of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Stanley B. Cohen Grant/research support from: AbbVie, Eli Lilly, Genentech, Gilead, Pfizer Inc, Consultant for: AbbVie, Eli Lilly, Genentech, Gilead, Pfizer Inc, Janet Pope Grant/research support from: Bristol-Myers Squibb, Roche, Seattle Genetics, UCB, Consultant for: AbbVie, Actelion, Amgen, Bayer, Bristol-Myers Squibb, Lilly, Merck, Novartis, Pfizer Inc, Roche, Sandoz, Sanofi, UCB, Boulos Haraoui Grant/research support from: AbbVie, Pfizer Inc, Consultant for: AbbVie, Amgen, Eli Lilly, Merck, Pfizer Inc, UCB, Fedra Irazoque-Palazuelos Consultant for: Bristol-Myers Squibb, Janssen, Pfizer Inc, Roche, UCB, Mariusz Korkosz Consultant for: AbbVie, Lilly, MSD, Novartis, Roche, UCB, Annette Diehl Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Jose Luis Rivas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Tatjana Lukic Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Shixue Liu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lori Stockert Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Noriko Iikuni Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Edward Keystone Grant/research support from: AbbVie, Amgen, Lilly Pharmaceuticals, Pfizer Inc, PuraPharm, Sanofi-Aventis, Consultant for: AbbVie, Amgen, AstraZeneca, Biotest, Bristol-Myers Squibb, Celltrion, Crescendo Bioscence, F. Hoffman-La Roche, Genentech, Gilead, Janssen, Lilly Pharmaceuticals, Merck, Pfizer Inc, Sandoz, Sanofi-Genzyme, Samsung Bioepis, UCB, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb Canada, F. Hoffman-La Roche, Janssen, Merck, Pfizer Inc, Sanofi-Genzyme, UCB